A Review of a Hair-Care Formulation for Hair Health - Monali G. Chaudhari; Tejaswini G Malge; Darshana Shirbhate; Vrushali Potdar (Asian Journal of Pharmaceutical Research and Development, 2025)
Hair plays a vital role in appearance, personality, and overall well-being, making its care an important aspect of cosmetic science. Hair is primarily composed of keratin and undergoes a natural growth cycle that can be influenced by genetic, physiological, and environmental factors. Damage to hair fibers occurs due to excessive use of chemical treatments, synthetic dyes, and environmental stress, which necessitates the development of effective and safer hair-care formulations. This review highlights the structure and physiology of hair, common causes of damage, and the role of cosmetic preparations such as shampoos, conditioners, oils, gels, and dyes in maintaining hair health. Particular emphasis is placed on herbal ingredients such as Amla, Shikakai, Henna, Hibiscus, and flaxseed, which demonstrate natural conditioning, coloring, antifungal, and strengthening properties. Modern advancements including silicone-based ingredients and optimized formulations provide improved manageability, shine, and protection against heat and chemical damage. Evaluation parameters such as foam stability, detergency, conditioning effect, viscosity, microbiological safety, and irritation studies are essential for assessing product performance. Overall, integration of natural extracts with modern cosmetic science offers a promising approach to achieving safe, effective, and consumer-friendly hair-care formulations.